Pengolahan Wadi Ikan Bawal Air Tawar (Colossoma macropomum) - Restu Restu (Fakultas Peternakan Universitas Kristen Palangka Raya, 2018)
“Wadi” is a processed product from fish or meat, through the salting process and added with samu as a medium for the growth of lactic acid bacteria, then followed by a fermentation process for 3 to 5 days, resulting in a distinctive aroma and mild sour taste of fermented products. Processing “wadi” of Tambaqui (Colossoma macropomum) was done to find out whether Tambaqui can be made into a wadi with a distinctive taste. The results showed that the wadi of Tambaqui was highly favored by panelists with organoleptic value (taste) = 7.66 on the hedonic scale with attractive appearance criteria, wadi distinctive odor but not too stinging, consistency of compact flesh and savory taste and not salty, nutritional value as follows: moisture content 58.74 %; protein content 21.75%; and fat content 0.60%. Keywords : Tambaqui (Colossoma macropomum), “wadi”, organoleptic test, nutritional value.